Ideal ratio of digestible methionine plus cystine to digestible lysine for growing Japanese quails - D’Avila Lima, Heder J; Bareto, Sergio LT; Donzele, Juarez L; Tinoco, Ilda FF; Ribas, Natália S (Revista Colombiana de Ciencias Pecuarias, 2015)
Background: methionine is considered essential for maintenance, growth, and feather development. Methionine supply during the growth phase can influence the weight at sexual maturity and egg size. Objectives: to evaluate the effects of several digestible methionine + cystine/digestible lysine ratios for growing Japanese quails (1 to 40 days of age) with repercussions on the early stage of production (41 to 110 days of age). Methods: a total of 1,000 one-day-old Japanese quails were randomly distributed to five digestible (methionine + cystine)/digestible lysine ratios, with 10 replicates and 20 birds per experimental unit. A basal diet formulated to meet all nutrient requirements was added with graded levels of DL-methionine replacing glutamic acid. Results: weight of the birds at 40 days, weight gain until 40 days, feed intake, carcass weight, fat, and bodyprotein deposition, methionine + cystine intake and birds viability in the growing phase presented a linear trend. A quadratic effect was observed for feed conversion and uniformity at 40 days of age, and percentage of feathers did not vary. A linear increase occurred in the laying phase for feed intake and weight gain of the birds. No effects of the assessed ratios were observed on the other variables. Conclusions: a 0.73 ratio of digestible (methionine + cystine) to digestible lysine in the growing phase provided uniform growth and satisfying performance of Japanese quails during the laying phase.